2018
DOI: 10.3390/ma11081480
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Residual Stress in Selective Laser Melting of a Zr-Based Amorphous Alloy

Abstract: An accurate estimation of residual stresses is crucial to ensure dimensional accuracy and prevent premature fatigue failure of 3D printed components. Different from their crystalline counterparts, the effect of residual stress would be worse for amorphous alloys owing to their intrinsic brittleness with low fracture toughness. However, the generation of residual stress and its performance in 3D printed amorphous alloy components still remain unclear. Here, a finite element method combined with experiments and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 55 publications
0
25
0
Order By: Relevance
“…Furthermore, surface areas are not large enough for placing the strain gauges needed for assessing stresses with the hole-drilling method [48]. Numerical simulations [5,53] and/or digital image correlation [53] would be required to measure the stress state, but this goes beyond the scope of our study. In crystalline alloys, such as SS316L [48], LSP results in plastic deformation of the near-surface region, leading to a change in residual stresses, but also in increased hardness and shrinking of porosities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, surface areas are not large enough for placing the strain gauges needed for assessing stresses with the hole-drilling method [48]. Numerical simulations [5,53] and/or digital image correlation [53] would be required to measure the stress state, but this goes beyond the scope of our study. In crystalline alloys, such as SS316L [48], LSP results in plastic deformation of the near-surface region, leading to a change in residual stresses, but also in increased hardness and shrinking of porosities.…”
Section: Discussionmentioning
confidence: 99%
“…Recent progress in laser powder-bed fusion (LPBF), the most widely used additive manufacturing (AM) technique for metals, has led to a strong interest in the manufacturing of bulk metallic glass (BMGs) [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15], since high local cooling rates induced by the LPBF process match the requirements for manufacturing BMGs with substantial dimensions and complex shapes [8]. This challenge generated a lot of enthusiasm due to the exceptional mechanical properties of BMGs, which make them possible candidates in a number of industrial fields, such as micro-mechanics, medicine, aerospace, and automotives.…”
Section: Introductionmentioning
confidence: 99%
“…According to Zhang et al (2019), the relief of residual stresses in additive manufactured Ti6Al4V by heat treatment or hot iso-static pressing (HIP) considerably improves its fracture toughness. Xing et al (2018) conducted an estimation of residual stresses in an SLM Zr-based alloy and observed that the effect of residual stress leads to its inherent brittleness with poor fracture toughness. Cain et al (2015) studied the crack propagation and fracture toughness of Ti6Al4V produced indifferent orientations by SLM.…”
Section: Discussionmentioning
confidence: 99%
“…Because the overhang A without any supports had been proven to be manufacturable by using SLM technology according to some previous experimental works, the teeth of the support A were deleted to prevent their effects on the final quality of the bottom surface of the overhang A. According to the research in [29], the residual stress is also determined by the overhang thickness and it becomes serious with increasing the overhang thickness. In our work, the overhang thickness (Figure 6a) is set as 2 mm.…”
Section: Experimental Methodsmentioning
confidence: 99%